Corporate social 'irresponsibility' as a case for inadmissibility in international investment arbitration: a new trend? - Monebhurrun, Nitish (My University, 2015)
International investment law is sometimes criticised because of its hemiplegic nature: a law field in which private companies have mostly rights whilst States bear all the obligations. This is, for instance, illustrated by the dispute settlement mechanism: in investment arbitration, the private investor is always the claimant and the State, the respondent. Notwithstanding the undoubted disequilibrium in the distribution of rights and obligations between investors and States, it must be recalled that this configuration was originally accepted and validated by all States. Evidence of a similar logic is found in Human Rights Law and before Human Rights Courts — where the State is always the defendant. If this comparison with Human Rights is, in principle, a valid one, it is true that many multinational companies can be as powerful as their host States in terms of financial capacity. But it is also true that the oft-discussed overprotection of investors by investment agreements tend to flee from the legal and technical aspects of investment arbitration. Indeed, under the shadow of a stricter scrutiny, the debate falls under other shades and reveals that the very access to arbitration is sometimes determined by a series of implicit duties incumbent upon private investors. These duties are now becoming explicit as per a new trend followed by recent bilateral investment agreements — signed, for example, by States like Canada, Brazil, Colombia, France —, which provide for corporate social responsibility (CSR). In some awards, arbitral tribunals have examined the investor's behaviour in order to grant access to arbitration, thereby upholding their claims as admissible or not. By this token, companies having established their activities by fraudulent means — misrepresenting their technical and financial capacity —, or by acts of corruption — bribing government officials — have been barred from petitioning on the merits. Such acts enter the realm of corporate social responsibility. In these awards, no texts existed that referred to CSR or to investors' duties. These where inferred by the arbitral tribunals by following the clean hands doctrine with the aim of protecting what they characterised as an international or transnational public policy. These cases bear testimony that an investor's socially irresponsible behaviour potentially blocks the admissibility of their claims. In this vein, invoking CSR as a case for (in)admissibility before arbitral tribunals is likely to develop as an accepted trend and technique if future investment agreements are shaped as the above-mentioned ones, which is something very probable. Agreements containing provisions on investors' protection standards on one hand, and on investors' corporate social duties on the other, are expected to be construed in an articulated and harmonious fashion so as to confer a purposeful effect — as per ut regis valeat quam pereat — to CSR. Within the logic of international investment arbitration, it is not as such a departure from CSR standards which bars an investor's claim; frustrating such standards implies that the company will come before the arbitral tribunal without clean hands. The latter is the legal technique which allows arbitrators to judge the claimant's locus standi and which accordingly brings CSR into the legal debate. It is this technical aspect of investment arbitration which this paper/intervention seeks to explore contending, furthermore, that a socially irresponsible investor who is nevertheless granted access to arbitration and to whom a favourable award is eventually rendered will, in law, be unjustly enriched. The paper/intervention will therefore be articulated as such: I. Corporate social irresponsibility acts as a bar to arbitration on the merits II. A claim which is considered admissible despite a corporate social irresponsibility unjustly enriches the claimant